WESTERN ETHNOCENTRISM IN IP MAN 2: LEGEND OF THE GRANDMASTER MOVIE - BASAREWAN, VIGI LESTARI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Every human being is derived from certain ethnic group. They grow up absorbing valuesand norms of that ethnic group. Every ethnic group usually has certain characteristics which distinguish one ethnic group to other ethnic groups. A group of people who merges in an areausually has the same characteristics such as physical appearance, behavior and perspective inseeing life. Therefore, ethnic group of someone can be recognized through those characteristics. Human being generally assumes their own ethnic group is better than other ethnic groups. Ithappens because they are proud of their ethnic group and tend to humiliate other ethnic groups.In Ip Man 2: Legend of the Grandmaster, the story describes ethnocentric attitudes of the Britons as the Western ethnic group toward Chinese ethnic group in colonialism periods inChina. The Western ethnic group underestimates Chinese ethnic group and whatever the Chinesehas done seems to be wrong. The Westerners use their own standards value to judge Chineseethnic group. Moreover, the Western ethnic group values are opposite from Chinese ethnicgroup.The ignorance of the West to accept Chinese culture triggers ethnocentric attitude of British ethnic group. They refuse to see the Chinese culture, tradition and belief from theChinese way of thinking. They use their standard which is different from Chinese ethnic group.Ethnocentric attitude of Western ethnic group causes negative stereotype and discriminationtoward Chinese ethnic group. The movie Ip Man 2: Legend of the Grandmaster contains manythemes that could be applied to conduct a research such as colonialism, unity and solidarity, andoriental despotism. The writer suggests the other English Literature students to conduct researchtoward this movie by using other theories that is related to those themes. Keywords: Western ethnocentrism, ethnic group, culture